An Environmental Language Approach for Increasing Behavior of Retarded Children - Mildred Odom; Rex R. Boatman; Dale D. Baum (Educational Considerations, 1973)
Immediate gains in four areas of language behavior of nine moderately retarded children, achieved through a systematic summer-camp-type activity program, remained significant one year later, report these authors.